Integrated immunodominant epitope discovery for dual-purpose rapid and economical diagnostic and immunoprotective applications against MRSA - Chen, Longlong; Yan, Pengju; Duan, LianLi; Ming, Guangyang; Wang, Xiaoqiong; Zhang, Jinyong; Chen, Zhifu; Gou, Qiang; Yuan, Yue; Jing, Haiming; Cheng, Ping; Luo, Ping; et al. (Frontiers in Immunology, 2025)
Current diagnostic and preventive strategies against Staphylococcus aureus methicillin-resistant strains (MRSA) remain inadequate. Hence, we aimed to identify candidate epitopes as potential therapeutic targets and diagnostic biomarkers. We focused on clinically validated targets and investigated four antigens (Hla, SEB, MntC, and IsdB) currently incorporated into phase III clinical trials of a recombinant five-antigen vaccine (termed rFSAV) and the recently identified leukocidin LukG. Using convalescent serum samples from patients with clinically confirmed MRSA, we identified 10 immunodominant epitopes through ELISA screening of overlapping 18-mer peptides, seven of which named MntC55-72, MntC121-138, MntC271-285, SEB37-54, LukG30-47, LukG235-252, and LukG246–263 have not been previously reported. Immunoprotection trials showed that five epitopes Hla168–185, IsdB384–401, MntC55–72, SEB37–54, and LukG235–252 elicited effective protection in a BALB/c murine sepsis model infected with MRSA252. The combination of these protective epitopes exhibited broad-spectrum efficacy against both the MRSA252 strain and phylogenetically distinct clinical isolates. Diagnostically, the performance of the epitope panel was superior to that of conventional culture methods with a sensitivity of 0.839 and specificity of 0.826 in a 3-h detection window, thus offering rapid and cost-effective advantages. Notably, bioinformatic analysis showed that all identified B-cell epitopes contained predicted CD4+ T-cell epitope sequences, which suggests the potential to elicit combined T–B cell immune responses through MHC-II presentation. Thus, these immunodominant epitopes with dual functions that integrate both diagnostic and immunoprotective capabilities could function as a novel immunodiagnostic toolkit that enables rapid MRSA detection and aid in establishing a multi-epitope vaccine platform. These findings present an integrated strategy that bridges diagnostic development and vaccine design for MRSA management.